I castighi del servo nella commedia antica - Donadio, Nunzia (Tesserae iuris, 2023)
Both in Plautus and in Menander there are numerous references to violence against slaves as an explanation of the unlimited punitive powers of the masters. This article analyzes the dramaturgical devices through which this violence against servants is introduced as comic violence in comedies, i.e. predominantly through the threat of punishment or the manifestation of fear of punishment by the slave. Several similarities are highlighted between the Plautine and Menandrian theaters in this field, starting with the reality of the domini-servants relationships represented in the Latin palliata and in the new Greek comedy.